Increased quinolone resistance among typhoid Salmonella isolated from Egyptian patients - Saleh, Fatma O.I.; Ahmed, Hazem A; Khairy, Rasha M.M.; Abdelwahab, Sayed F. (The Journal of Infection in Developing Countries, 2014)
Introduction: Typhoid fever is endemic in Egypt; and quinolones are the empirical treatment of choice. There are very limited data reporting quinolone resistance among Egyptian typhoidal Salmonella isolates. We previously reported that all typhoidal Salmonella were sensitive to quinolones. This study aimed to isolate and identify typhoidal Salmonella from cases suffering from enteric fever at Minia Governorate, Egypt, determine their quinolone resistance patterns, compare them to those reported 20 years ago, and test gyrA mutation as a possible mechanism for quinolone resistance. Methodology: Stool samples from Widal-positive subjects were screened by culture on suitable media and were identified biochemically. The identified isolates were tested for resistance against three representatives of the first three quinolone generations, namely nalidixic acid (NAL), levofloxacin (LEV), and norfloxacin (NOR). The gyrA gene was amplified and sequenced to detect point mutation(s) conferring quinolone resistance. Results: Out of 230 stool samples (from patients with Widal anti-O titers of ≥ 1/160), 40 isolates were S. enterica serovar Typhi (97.5%) and Paratyphi A (2.5%). Six (15%) isolates were resistant to at least one of the quinolones, compared to 0% in 1993. In this regard, 15%, 7.5%, and 2.5% of the isolates were resistant to NAL, both NAL and LEV, and all three quinolones tested, respectively. Sequencing of the gyrA gene revealed point mutations at position 83 and/or 87 of the gyrA gene only among the resistant isolates. Conclusion: There has been an increase in quinolone-resistant typhoidal Salmonella in Egypt over time.